2014
DOI: 10.1177/1532673x14535239
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Race, Ethnicity, and Party on Attitudes Toward Descriptive Representation

Abstract: Using original survey data from the Cooperative Congressional Election Survey (CCES), we examine variation in racial and ethnic group and partisan attitudes toward legislators and representation. Respondents were asked about their views on descriptive representation, its importance for their own elected official, and whether it was important to have more descriptive representatives in general. Using respondents’ personal characteristics such as education, partisanship, race, ethnicity, income, and race and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…However, it is possible that Latino Republicans may have felt differently on immigration because of the personal nature of the issue for the Latino community. The role of partisanship amongst Latinos has consistently explained Latino political attitudes with Republicans demonstrating different policy positions and attitudes than their Democratic counterparts (Abrajano and Alvarez 2010;Casellas and Wallace 2015).…”
Section: Republicansmentioning
confidence: 99%
“…However, it is possible that Latino Republicans may have felt differently on immigration because of the personal nature of the issue for the Latino community. The role of partisanship amongst Latinos has consistently explained Latino political attitudes with Republicans demonstrating different policy positions and attitudes than their Democratic counterparts (Abrajano and Alvarez 2010;Casellas and Wallace 2015).…”
Section: Republicansmentioning
confidence: 99%
“…Moreover, Casellas and Wallace (2015) show that both Latinos and blacks have strong preferences for more descriptive representation in Congress. The elevated social pressure to turnout to increase diversity in government may lead blacks and Latinos who have the potential to be descriptively represented to feel ashamed for staying home on Election Day.…”
Section: The Over-reporting Of Votingmentioning
confidence: 97%
“…This finding suggests that the notion of surrogate representation is meaningful to people and they respond positively to the idea that their group has a voice in the legislature, regardless of whether that voice comes from their own district. More recently, Casellas and Wallace () found that Latinos and blacks were more likely than whites to say that having more co‐ethnic representatives in Congress is important. Their study, however, was unable to assess the mechanisms underlying the ethnic group differences.…”
Section: The Concept Of Surrogate Representationmentioning
confidence: 99%
“…The second is partisan identification. As most Latino elected officials are Democrats, perhaps Latinos who are Republican do not feel that Latinos in Congress represent them (Casellas and Wallace, ). Next is a dummy variable that indicates if the respondent and his or her representative are from the same political party, since it is plausible that people whose representatives are from a different party might be especially likely to feel like they need to look elsewhere for representation.…”
Section: Data and Measuresmentioning
confidence: 99%